Preferences of public space users towards trees and other forms of greenery in Lublin's old town - Trzaskowska, Ewa; Renda , Joanna; Adamiec, Paweł; Kułak, Agnieszka (Bulletin of Geography. Socio-economic Series, 2023)
Currently, the functions of the historical parts of cities are more and more oriented towards the visitors rather than residents. The high density of cultural heritage objects attracts tourists for whom restaurants and shops are created. Therefore, the management and planning of the historic parts of cities has become an increasing challenge. At the same time, activities aimed at improving the quality of life in the city centre, including the most built-up historical parts, require the introduction of greenery (Kowarik, 2019). In order for such spaces to be effective, we require a greater understanding of user preferences. The aim was to define preferences regarding the presence and use of various forms of greenery and their acceptance in the space of the old town. We also asked a question about the functions of the greenery. The study was conducted using an online survey in Lublin, Poland. The method of virtual development of 4 public spaces presenting various forms of greenery in a built environment was used. It was found that the presence of green elements and their form are very important. Trees in particular have a strong influence on preferences, suggesting that they deserve more attention in historical spaces in cities. Flower beds, plants in pots are accepted. The results show that the current level of development is unsatisfactory, and the respondents point out the need to introduce more greenery. Respondents' preferences related to greenery forms depend mainly on gender and age. Especially women and younger age groups preferred spaces with aesthetically attractive elements, such as flowering herbaceous plants in pots. Most of the respondents declared the use of space as places of rest and recreation, and indicated the climatic, ecological and aesthetic functions as important factors in assessing historical spaces in cities. The results should be taken into account by specialists in urban design in historical spaces subject to revitalization.